Bank-Based Financial Development and Economic Growth in Nepal - Lamichhane, Dipak Raj (Journal of Development Review, 2024)
The study of causal relationship between Nepal’s economic growth and bank-based financial development was carried out by using time series data since 1964. The Granger causality test was applied to measure the causality between the bank-based financial development and economic growth. The proxy variable for bank-based financial development are: private sector credit by Banks and Financial Institutions to GDP, bank deposits mobilized by BFIs to GDP, inflation – an indicator for macroeconomic stability. Inflation is also a variable inserted to cater omitted variable in this study. The objective of the research and findings are: private sector credit by Banks and Financial Institutions to GDP and bank deposits mobilized by BFIs to GDP do not cause economic growth individually but including, inflation – an indicator for macroeconomic stability and a variable inserted to cater omitted variable in this study, causes economic growth. Economic growth causes bank deposits to increase. Economic growth does not cause private sector credit to increase. Similarly, gross capital formation also contributes to economic growth in Nepal.